Reformasi Birokrasi Wali Kota Yogyakarta 2001 – 2011: Telaah Semiotika - Budi Puspo Priyadi; Teuku Afrizal (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
The presence of a leader in the Indonesian bureaucratic arena is of significant importance to patrimonial society. As a result, the Indonesian bureaucracy's character is more concerned with the interests of the elite than the people. This was also influenced by the bureaucratic model of colonial and the kingdom. When reformation struck Indonesia in 1998, the character of the Indonesian bureaucracy was no longer suitable with the demands of people in the post-reform era. This study examines the presence of a figure from merchants in the arena of the Indonesian public bureaucracy i.e the Mayor of Yogyakarta. In the midst of lack of leaders serving the people, this figure has drastically changed the context of public service with the idea of